A61 USE OF ADJUNCTIVE REMOVAL TECHNIQUES FOR ENDOSCOPIC MUCOSAL RESECTION OF LARGE NON-PEDUNCULATED COLONIC POLYPS IS PREDICTIVE OF POLYP RECURRENCE. (4th March 2021) - Li, S; Mosko, J; May, G; Kandel, G; Kortan, P; Marcon, N; Teshima, C
Abstract: Background: Endoscopic mucosal resection (EMR) allows for safe and effective removal of large non-pedunculated colon polyps. However, prior studies have shown significant recurrence rates between 10–30% after EMR, which have led to recommendations for close endoscopic follow-up and the use of techniques such as snare tip soft coagulation (STSC) to EMR margins to prevent recurrence. Models such as the Size/Morphology/Site/Access score (SMSA) have been developed to aid in identifying polyp complexity and patients at high risk of recurrence. Numerous individual risk factors for recurrence have previously been reported, however the significance of these factors have varied between studies, with limited data from Canadian centres. Aims: To evaluate predictors of recurrence for large non-pedunculated polyps following EMR. Methods: Consecutive patients between April 1, 2017 to March 1, 2019 who underwent EMR were retrospectively identified from endoscopy unit administrative records. Patients with non-pedunculated colorectal polyps ≥ 2 cm that were removed by EMR were included if follow-up endoscopy data were available. Polyps found to contain invasive adenocarcinoma on histology and/or were referred for surgical resection were excluded. Patient demographic, pre-procedural, intra-procedural, and post-procedural data to time of first follow-up colonoscopy were extracted. Recurrence was defined as a positive pathology specimen from the EMR scar at follow-up. Adjunctive techniques were defined as the use of any non-snare resection or ablation technique for removal of visible adenoma at the time of the EMR. Chi-square and multivariate regression analyses were conducted for variables of interest. Results: 517 patients underwent large polyp EMR during the study time period with 265 patients satisfying inclusion criteria. Median age of patients was 67 years (IQR 14); 48% were female. STSC was performed to EMR margins in 94% of cases. 30.9% and 69.1% of polyps were SMSA grade 3 and grade 4 respectively. Adjunctive removal techniques were utilized in 31% of patients, 95% of which was hot avulsion. 15% of patients had recurrence on follow-up endoscopy. Higher SMSA grade was associated with the use of adjunctive techniques (20% vs. 37%, p=0.006). The use of adjunctive removal techniques (OR 2.92, p=0.007) and male gender (OR 3.45, p=0.002) were the only factors found to be significantly predictive of recurrence on multivariate analysis. Conclusions: Male gender and the use of adjunctive removal techniques, particularly hot avulsion, are independently predictive of recurrence after EMR of large complex colorectal polyps. Male patients and those who require hot avulsion may be considered high risk for recurrence and warrant closer follow-up. Funding Agencies: None